Eliza: Guerilla Art Supports Heritage Value - Harris, Jennifer (Promaco, 2009)
There is extensive commentary on the role of public, unauthorised art in western cities, but little on the coincidence of heritage value and guerilla art. This paper analyses the relationship of the two in a statue of a 1940s swimmer entitled Eliza which was unveiled in the Swan River in Crawley, Perth in 2007. It commemorates the Crawley Baths which from 1914 to their demolition in 1964 were one of Perth’s premier meeting places. Eliza was commissioned by the Perth City Council as a monument to a lost place. Since its appearance, however, the statue has functioned not just as a place of memory, but dominantly of guerilla art and public comment. These activities foreground the transgressive potential of the coincidence of a heritage marker and guerilla art. Reading the Australia ICOMOS Burra Charter 1999, however, alongside Eliza shows that interpretation which foregrounds transgression is incomplete. The steadily strengthening professional heritage emphasis on social value over the previous dominance of original fabric, suggests that the delight and frivolity - but crucially not vandalism - with which the statue has been greeted, supports evolving heritage practice.